Using BWRO for removal of Arsenic III from anaerobic groundwater - A.H. Haidari; T. van Dijk; W.G. Siegers; T. Rijnaarts; E.R. Cornelissen (Desalination and Water Treatment)
Arsenic in groundwater poses significant health risks, especially in regions dependent on groundwater for drinking water. This study compares the performance of two brackish water reverse osmosis membranes for arsenic (III) rejection. The study explores membrane performance under conditions not extensively addressed before, such as using natural anaerobic groundwater with arsenic concentrations of 70–80 µg/L and examining the effect of sulfide complexation on arsenic rejection. The impact of sodium sulfide and antiscalant on arsenic rejection was investigated, with Na₂S tested as a complexing agent. The aim was to determine whether antiscalant addition affects sulfide stability or arsenic rejection, and whether it could lead to decreased membrane efficiency in the short term. Results show that membrane type contributes to a 5–8 % difference in arsenic rejection. Arsenic rejection mirrored boron’s trend but was consistently higher. However, the addition of sodium sulfide, with or without the antiscalant, did not enhance arsenic rejection, indicating that membrane type remains the primary factor. These findings highlight the need for tailored membrane selection to optimize arsenic rejection under anaerobic conditions. Chemical treatment strategies should align with specific contaminant profiles and feedwater conditions, with further pilot-scale validation for real-world applications.